ASSESSMENT OF ENZYMURIA FROM PROXIMAL RENAL TUBULE IN INFLAMMATORY SERONEGATIVE RHEUMATOID ARTHRITIS - Spasovski, Dejan; Sandevska, Emilija; Genadieva Stavrikj, Sonja; Krstevska Balkanov, Svetlana; Ana Vasilevska; Lindita Xhemaili Jakupi; Elena Cvetinovska; Kujtim Iseini; Vladimir Mitreski; Nikola Chamurovski; Jakimovska Dimitrovska, Maja (Macedonian Medical Association/De Gruyter, 2022)
Introduction. To determine the effects of non-treated seronegative rheumatoid arthritis (RA) on proximal renal tubule, sensitivity of alanine aminopeptidase (AAP), -glutamyltransferase (--GT), β2 microglobulin in urine β2M), as well as to determine the relation with rheu-matoid factor (RF) and C-reactive protein (CRP), DAS 28 - disease activity score. Methods. RF was determined by agglutination test (latex RF test, while kinetic methods were used for determination of alanine aminopeptidase (AAP) and -glutamyltransferase (-GT), as well as MEIA (micro-particle enzyme immunoassay) to determine β2 micro-globulin in urine. Samples (serum and urine) of 70 participants were examined (35 RA not treated, 35 healthy control group of patients). Results. In 35 RF negative RA, AAP enzymuria was present in 12 (34.28%) patients, -GT was present in 7 patients (20%), while β2 microglobulin was present in 3 patients (8.57%). In the healthy control group, 4 patients showed AAP positivity (11.42%), 2 patients -GT positivity (5.71%) and 1 patient showed presence of 2 microglobulin in urine (2.85). RF was not detected in any patient (0%). Conclusion. AAP has a higher sensitivity of -GT and β2 microglobulin in the detection of asymptomatic renal lesions in non-treated seronegative RA.
PROCENKA NA ENZIMURIJA OD PROKSIMALNA RENALNA TUBULA KAJ VOSPALITELEN SERONEGATIVEN REVMATOIDEN ARTRITIS
Keywords: alanine aminopeptidase, (AAP); glutamyl transferase (--GT); β2 microglobulin (β2M); rheumatoid arthritis (RA); rheumatoid factor (RF)